Migraciones humanas en la quebrada del Toro (departamento Rosario de Lerma, provincia de Salta). Período 1947-2001 - Barbarán, Francisco R. (2013)
Using census information, we verified that quebrada del Toro’s population diminished 35% between 1980 and 2001. In Rosario de Lerma Department, the rural population was 75% in 1947 and 25% in 2001. Considering urban inhabitants, that percentage was exactly the opposite. The weak productive structure and the isolation promote the emigration. On the other hand, the Indian claims for lands, show that not everybody wants to leave. So, it is necessary the implementation of development projects, using the renewable natural resources in a sustainable way, within viable economic and social objectives.